Prevalence and antimicrobial susceptibility of helicobacter pylori and associated factors among symptomatic Patients at Butagaya health center iii, Jinja district - Apeduno, Lucy; Kaiga, Manusuli; Kasumba, Expedito; Kyakulaga, Adonia; Omar, Ambrose James; Kalyetsi , Rogers; Sempijja, Fred; Rudolf, Buga; Gumisiriza, Robert; Nyiramahoro, Salome (Student’s Journal of Health Research Africa, 2025)
Background: H. pylori infection rates are higher in resource-poor settings and developing countries such as Uganda. Despite the fact that most health facilities in Uganda including government health facilities have put in place a number of measures including diagnostic methods for H. pylori and antibiotics used in treatment and management of H. pylori infection, Methods: The study employed a cross-sectional design that involved 384 individuals at the Outpatient department at Butagaya Health Centre III, who presented with signs and symptoms of H. pylori infection; selected using simple random sampling. H. pylori antigen tests, an interviewer administered structured questionnaire and disc diffusion were used to obtain data, Results: The study found that 22.4% of respondents were positive H. pylori tests. However, growth was only registered on 9(10.5%) of which, 4(44.4%) were susceptible and 5(55.6%) were resistant. Of the resistant samples, 1(20.0%) was resistant to Clarithromycin, 2(40.0%) to Metronidazole, 1(20.0%) to Levofloxacin and 1(20.0%) to Tetracycline; 2(40.0%) were resistant to only one antibiotic, 2(20.0%) had dual resistance (1(50.0%) to Clarithromycin and Metronidazole, 1(50.0%%) Levofloxacin and Metronidazole) while 1(20.0%%) had multiple resistance to Clarithromycin, levofloxacin and metronidazole. Age, gender, marital status and source of drinking water had a significant association with H. pylori infection (p<0.05). Conclusion: The prevalence of H. pylori was established at 22.4%. Full susceptibility to antibiotics was established at 44.4%. The highest resistance was to Clarithromycin and dual resistance to Clarithromycin + Metronidazole and Levofloxacin + Metronidazole. Age, marital status, gender and source of drinking water were the only factors found to be significantly associated with H. pylori infection Recommendations: Individuals should take care to obtain water from safe sources, culture and sensitivity should always be performed for all suspected H. pylori infections and clinical trials should be done to guide the development of new antibiotics